2013
DOI: 10.4103/0976-9668.107262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective role of vitamin C in imidacloprid-induced hepatotoxicity in male Albino rats

Abstract: In the present study, the effects of oral administration of imidacloprid for 4 weeks on serum biochemical, oxidative stress, histopathological and ultrastructural alterations were assessed in the liver of male rats. This study also aimed to investigate whether vitamin C could protect against the imidacloprid-induced oxidative stress. Forty-eight male Sprague dawley rats were divided into four groups of 12 animals each. Group 1 served as the control, while groups 2 and 4 were administered with imidacloprid (80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…It is of interest to know that there was a significant reduction in the body weight of high dose exposed mice. The decrease in body weight is inconsistent with the previous studies [11] , [25] . Badgujar et al stated that the high exposure of imidacloprid resulted in decreased body weight and other pathological changes in BALB/c mice [26] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is of interest to know that there was a significant reduction in the body weight of high dose exposed mice. The decrease in body weight is inconsistent with the previous studies [11] , [25] . Badgujar et al stated that the high exposure of imidacloprid resulted in decreased body weight and other pathological changes in BALB/c mice [26] .…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in agreement with Kammon and colleagues [16] . The hepatotoxic effects noted here are in agreement with the findings of soujanya et al [25] .…”
Section: Discussionsupporting
confidence: 93%
“…Atasayar et al [79] demonstrated that combined treatment of vitamin C and E with single acute dose (toxic dose) of cisplatin is able to normalize the histopathological alteration induced by cisplatin on kidney when compared with cisplatin alone treated group. The mechanisms by which ascorbic acid decreases the hepatotoxicity induced by cisplatin, is embodied in the fact that ascorbic acid might ameliorate the oxidative damage by decreasing LPO and altering antioxidant defense system [80] , [81] .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, brain sections of rats treated with 80 mg/kg body weight revealed marked congestion in cerebellum, degeneration of Purkinje cells with loss of dendrites, vacuolation around neurons, and shrunken neurons on 14 th day of experiment. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%